2022
DOI: 10.1002/iid3.692
|View full text |Cite
|
Sign up to set email alerts
|

HDAC4 depletion ameliorates IL‐13‐triggered inflammatory response and mucus production in nasal epithelial cells via activation of SIRT1/NF‐κB signaling

Abstract: Introduction Allergic rhinitis (AR) is frequently known as a chronic respiratory disease with a global high prevalence. The pivotal roles of histone deacetylase 4 (HDAC4) in multiple human diseases have been underlined by numerous studies. Nevertheless, whether HDAC4 is implicated in AR remains to be elaborated. The objective of the current study is to clarify the impacts of HDAC4 on AR. Methods First, human nasal epithelial cells (hNECs) were pretreated by interleukin‐13 (IL‐13). HDAC4 expression in hNECs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
1
0
0
Order By: Relevance
“…Here, we discovered SIRT5 overexpression mitigated cell apoptosis in IL-4/IL-13-treated NEpCs, suggesting the potential anti-apoptotic activity of SIRT5 in AR, which was also in line with that of glucolipotoxicitytreated pancreatic β cells and cisplatin-treated kidney cells [46,47]. SIRT5 function in AR was likewise consistent with SIRT1, another member of SIRT family [48]. Furthermore, we investigated the relationship between miR-205-5p and SIRT5 and discovered that miR-205-5p targeted SIRT5 in AR.…”
Section: Discussionsupporting
confidence: 81%
“…Here, we discovered SIRT5 overexpression mitigated cell apoptosis in IL-4/IL-13-treated NEpCs, suggesting the potential anti-apoptotic activity of SIRT5 in AR, which was also in line with that of glucolipotoxicitytreated pancreatic β cells and cisplatin-treated kidney cells [46,47]. SIRT5 function in AR was likewise consistent with SIRT1, another member of SIRT family [48]. Furthermore, we investigated the relationship between miR-205-5p and SIRT5 and discovered that miR-205-5p targeted SIRT5 in AR.…”
Section: Discussionsupporting
confidence: 81%
“…In nasal epithelial cells, the HDAC4 profile was elevated upon IL-13 treatment, which repressed SIRT1 and initiated NF-κB signaling. HDAC4 knockdown activated SIRT1/NF-κB signaling and mitigated inflammatory responses and mucus generation in nasal epithelial cells after IL-13 treatment [39]. NF-κB, an indispensable transcription factor, plays a pivotal role in the modulation of IL-1β-elicited cell viability, migration, apoptosis, and inflammatory response in both human chondrocytes and NP cells [40][41][42].…”
Section: Discussionmentioning
confidence: 97%
“…IL-13 secreted by Th2 cells is considered to be a central mediator of allergic inflammation, stimulating mucin synthesis and secretion ( 80 ). Studies have shown that IL-13 can induce inflammatory responses and mucus secretion in human nasal epithelial cells (hNEC), and the severity of AR can be determined based on the expression of IL-13 ( 81 ). Nrf2 and Kelch-like ECH associated protein (Keap 1) combine as dimers in the cytoplasm.…”
Section: Allergic Rhinitismentioning
confidence: 99%
“…Consistent with this, SIRT1 mediates acetylation modification of NF-κB p65, inactivating the NF-κB pathway ( 86 ). Interfering with HDAC4 can restore the expression of SIRT1 and reduce the inflammatory response caused by IL-13 by activating the SIRT1/NF-κB pathway ( 81 ).…”
Section: Allergic Rhinitismentioning
confidence: 99%